2017
DOI: 10.1371/journal.pone.0186296
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants and traits related to insulin-like growth factor-I and insulin resistance and their interaction with lifestyles on postmenopausal colorectal cancer risk

Abstract: Genetic variants and traits in metabolic signaling pathways may interact with lifestyle factors such as obesity, physical activity, and exogenous estrogen (E), influencing postmenopausal colorectal cancer (CRC) risk, but these interrelated pathways are not fully understood. In this case-cohort study, we examined 33 single-nucleotide polymorphisms (SNPs) in genes related to insulin-like growth factor-I (IGF-I)/ insulin resistance (IR) traits and signaling pathways, using data from 704 postmenopausal women in Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…It has been reported that the modification in the individual values of plasma insulin levels due to diet may affect the risk of suffering from colorectal cancer [61]. A similar result was found by other researchers in a study performed with a sample of postmenopausal women [62]. Although there are many studies in this line [63,64] and it is known that genetic variants in metabolic signaling pathways may interact with lifestyle factors such as dietary fatty acids influencing colorectal cancer risk, these interrelated pathways are not fully understood [65].…”
Section: Discussionsupporting
confidence: 78%
“…It has been reported that the modification in the individual values of plasma insulin levels due to diet may affect the risk of suffering from colorectal cancer [61]. A similar result was found by other researchers in a study performed with a sample of postmenopausal women [62]. Although there are many studies in this line [63,64] and it is known that genetic variants in metabolic signaling pathways may interact with lifestyle factors such as dietary fatty acids influencing colorectal cancer risk, these interrelated pathways are not fully understood [65].…”
Section: Discussionsupporting
confidence: 78%
“…An interesting study by Hu et al [40] indicated that IGF-1 gene expression levels were higher in patients with concomitant MS and CRC than in patients with CRC without MS. In addition, it has been demonstrated that specific single nucleotide polymorphisms (SNPs) of genes within IGF-1/IR traits, in interaction with modifiable lifestyle factors, affect CRC risk in postmenopausal women [55]. Moreover, a possible synergistic effect on CRC risk in postmenopausal women was reported for IR-associated SNPs LINC00460 rs1725459 and MTRR rs722025 in combination with estrogen/oral contraceptive use and smoking [56].…”
Section: Insulin Resistancementioning
confidence: 99%
“…Given the well-established role of IGF132 and the role of the somatostatin-signaling axis33,34 in promoting and impeding tumorigenesis, respectively, the anticancer activity of octreotide is not a surprising finding. Indeed, radiolabeled octreotide currently has a diagnostic application in oncology, allowing the detection of SSTR-positive tumors via scintigraphy (octreoscan).…”
Section: Overview Of Current Clinical Use Of Octreotide and Chloroquimentioning
confidence: 99%